Exploring the Impact of Podcasts on Millennial Engagement with Islamic Teachings - Salman Farid, Ahmad (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This research explores the impact of podcasts on millennial engagement with Islamic teachings, investigating how this digital medium influences religious education, community-building, and identity formation. Through interviews, surveys, and content analysis, the study reveals that podcasts play a significant role in enhancing accessibility to Islamic knowledge, offering millennials a flexible and personalized avenue for learning and exploration. Diverse content preferences among millennials highlight the importance of tailoring podcast content to meet the varied needs of the audience, ranging from theological discussions to practical advice on applying Islamic principles. Moreover, Islamic podcasts foster online communities where millennials connect, seek guidance, and engage in religious discourse, strengthening their commitment to faith and promoting social connection. Trust in podcast hosts and content creators emerges as a key factor influencing millennials' engagement and shaping their religious beliefs. Furthermore, podcasts featuring global perspectives contribute to intercultural understanding and appreciation for the diversity within the Muslim community. While podcasts offer numerous benefits for millennial engagement with Islamic teachings, challenges such as content quality and misinformation underscore the importance of addressing these issues to maximize the educational value and impact of Islamic podcasts in the digital age.